Impact of Austropuccinia psidii in New Caledonia, a biodiversity hotspot. Issue 2 (2nd December 2017) - Soewarto, J.; Carriconde, F.; Hugot, N.; Bocs, S.; Hamelin, C.; Maggia, L.
Summary: Myrtle rust, caused by the fungus Austropuccinia psidii, infects a wide range of host species within the Myrtaceae family worldwide. Since its first report in 2013 from New Caledonia, the extent of the host range, geographical distribution and genetic diversity of A. psidii in this territory have been unknown. This study reports 67 new host species distributed in 13 different Myrtaceae genera, including five new genera. The pathogen was found in various types of plant communities, where Myrtaceae species are the dominant or codominant species, as well as in several nurseries. It is now considered a significant threat to the biodiversity of ecosystems and the Myrtaceae‐related economy. A 3‐year disease monitoring trial with 35 cultivated Myrtaceae species showed variations in disease severity at the species and individual scales. This suggests that some level of genetic resistance to myrtle rust may possibly exist among the endemic Myrtaceae of New Caledonia. A population genetic investigation revealed that only one single genotype of A. psidii occurs across its entire host range in New Caledonia. Therefore, it is essential to carry out population genetic surveillance to identify the appearance of mutations or the introduction of potentially more virulent genotypes of A. psidii . The outcomes from this study will assist with the ongoing management of the disease in New Caledonia.